CELLULAR AUTOMATA MICROSIMULATION IN MODELING THE SPREAD OF DISEASE - SUGIARTO (NIM : 10109083); pembimbing : Dr. Nuning Nuraini, WILLY
The pattern of spread of disease can be represented in a mathematical model. Using cellular automata, we can get an image from the pattern of spread of disease. In this paper, the simulation spread of disease is established considering the individual that can move factors and the spread of disease factors. The main problem in determining the distribution pattern of disease is about how to get the algorithms that can show pattern of spread of disease explicitly. Construction of algorithms can be divided into two parts, algorithms for simulating individuals that can move by using the principle of autonomous agents and algorithms for simulating the spread of disease using cellular automata. Discussion of the comparison between cellular automata models that provide spatial description and model of SIR (Susceptible, Infected, Recovered) which gives a description deterministically reviewed in the last chapter.